Solving ordinary differential equations I - Hairer, E. q (Ernst) (Springer series in computational mathematics, 1993)
This book deals with methods for solving nonstiff ordinary differential equations. The reader will benefit from many illustrations, a historical and didactic approach, and computer programs. This new edition has been rewritten and new material has been included